Which is a stronger predictor of the abundance of Dorcas Gazelle, Gazella dorcas in the Eastern desert of Egypt: human or natural factors?. Issue 3 (3rd July 2022) - Nagy, Abdullah; Mohallal, Eman M. E.; El-Kafrawy, Sameh; Saber, Samy A.
Abstract : The Dorcas Gazelle, Gazella dorcas, has lost 86% of its global historical range, and is regionally categorized as endangered by the IUCN. The factors that caused this decline have never been quantified. In this work, field and remotely sensed data were used to examine the ecological and anthropogenic factors affecting the abundance of Dorcas Gazelle within Wadi El-Gemal Protected Area in the Eastern desert of Egypt, using Generalized Linear Mixed Models (GLMM). The species' abundance is shaped by anthropogenic activities (number of car trails and proximity to the coastal road) more than ecological factors (vegetation and wetness indices). Dorcas Gazelle is avoiding more humid and greener areas because of human disturbance. Such suitable habitats may be perceived by gazelles as too dangerous, and the animals therefore prefer less suitable but safer habitats that are further away or less frequented by humans. Moreover, an easy to conduct, cheap monitoring tool, the Kilometric Abundance Index (KAI), was devised and implemented for baseline information to be used for future monitoring of Dorcas Gazelle.